2015
DOI: 10.1073/pnas.1518376112
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal development, growth control, and homeostasis in the face of centrosome amplification

Abstract: As nucleators of the mitotic spindle and primary cilium, centrosomes play crucial roles in equal segregation of DNA content to daughter cells, coordination of growth and differentiation, and transduction of homeostatic cues. Whereas the majority of mammalian cells carry no more than two centrosomes per cell, exceptions to this rule apply in certain specialized tissues and in select disease states, including cancer. Centrosome amplification, or the condition of having more than two centrosomes per cell, has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 60 publications
2
50
0
Order By: Relevance
“…3 I and J). Similarly, an increase in Plk4 RNA drove centrosome amplification in 20% of keratinocytes within the skin epidermis (26). However, despite 4-fold and 30-fold elevations, respectively, in the level of Plk4 transcripts in lung and kidney ( Fig.…”
Section: Supernumerary Centrosomes Promote Chromosome Segregation Errorsmentioning
confidence: 84%
See 1 more Smart Citation
“…3 I and J). Similarly, an increase in Plk4 RNA drove centrosome amplification in 20% of keratinocytes within the skin epidermis (26). However, despite 4-fold and 30-fold elevations, respectively, in the level of Plk4 transcripts in lung and kidney ( Fig.…”
Section: Supernumerary Centrosomes Promote Chromosome Segregation Errorsmentioning
confidence: 84%
“…Thus, in mice with active p53, Cre-mediated activation of Plk4 overexpression is sufficient to drive centrosome amplification in permissive tissues, including the liver (Fig. 3) and skin (26). Nevertheless, cohorts of Plk4-overexpressing mice showed no difference in overall survival compared with control animals (Fig.…”
Section: Supernumerary Centrosomes Promote Chromosome Segregation Errorsmentioning
confidence: 95%
“…While initial studies failed to observe the development of spontaneous tumors in animals with widespread PLK4 overexpression 156,158,159 , a more modest increase in PLK4 levels was shown to promote persistent centrosome amplification that promoted the development spontaneous tumors 147 . Importantly, these tumors exhibited dramatic numerical and structural chromosomal alterations, mirroring the complex karyotype changes frequently observed in human tumors with extra centrosomes 147 .…”
Section: Centrosome Defects and Cancermentioning
confidence: 99%
“…In another study, the same group found that mice overexpressing PLK4 in the basal layer of the epidermis exhibited a 20% increase in basal and suprabasal epidermal cells with CA; an increase in multiciliated basal cells; an increase in spindle alignment defects in basal cells due primarily to uncoupling of the spindle from cortical cues; an increase in spindle multipolarity, aneuploidy, and DNA damage in embryonic epidermal tissue; and defective stratification and growth of embryonic epidermal tissue, which was minimally rescued by p53 knockdown (Kulukian, et al 2015). Despite these defects, PLK4-overexpressing mice had normal epidermal barrier function and architecture and similar overall and tumor-free survival compared with control mice.…”
Section: Centrosome Amplification and Breast Tumorigenesismentioning
confidence: 99%